Passing plastic: traces of plastic in the fecal samples of a high Arctic seabird in Tunu (East Greenland) - Justine Ammendolia; Garth A. Covernton; Alexandra Skrepnyk; John F. Dower; Shoshanah Jacobs (Arctic Science)
Arctic seabirds are key bio-indicators of marine plastic pollution due to their transient movement and large populations. Although many studies have quantified the ingestion of microplastic particles (<5 mm in size) through necropsy or regurgitation sampling methods, little is known about post-digestive particle excretion. Due to the logistical challenges of non-lethally sampling feces from Arctic seabirds, this pathway remains largely understudied. We non-lethally collected 110 fecal samples from little auks (Alle alle) during the 2014 breeding season in Ukaleqarteq, Tunu (Kap Höegh, East Greenland). We identified 25 potential microplastic particles (>100 µm in size), 19 of which were analyzed for material composition using Fourier Transform Infrared Spectroscopy and Raman micro-spectroscopy. Of these, 13 particles were successfully matched to materials, with five as plastic. This produced an average concentration of 0.08 ± 0.28 microplastic particles per fecal sample, with no difference of occurrence between chicks and adults. Particle lengths ranged from 113 to 751 µm. The presence of microplastics larger than our lower limit of detectability of 100 µm suggests a need for analysis of smaller particles and microfibers in this species. We contribute to understanding how microplastics pass through little auks and characterize how this species interacts with the plastic pathways.